Proposed new interior design for Ayam Penyet Restaurant at Lot C-G-1, Greentown Suria, at Jalan Dato’ Seri Ahmad Said, 30450 Ipoh Perak / Nor Haiza Kasim - Kasim, Nor Haiza (Faculty of Architecture, Planning and Surveying, 2010)
Final project for Diploma in Interior Design students is manifestation of candidate understanding about all aspect of interior design project from the basic stage till the final presentation proposed design. Proposed design project for final project of candidate chosen is proposed new interior design for Ayam Penyet Restaurant at Lot, C-G-1. Greentown Suria, of Jalan Dato’ Seri Ahmad Said, Ipoh Perak. There are many complications and issues which have to be considered as primary solution for acquiring general interior design’s concepts and images. As main factors, space requirement, themes, and area usage as well as several aspects are important and have to exist in designing restaurant. Research methodology use in seeking the information required in find solution by interviews and meeting, surveys and questionnaires, case study and observations. To create spatial design providing suitable space for worker or staff to be a good worker and get more easy facilities to settle down their liability. Research can be defined as the search for knowledge or any systematic investigation to establish facts. Site proposed at Greentown Suria located at the middle of the Ipoh as Multimedia Super Corridor city. From comparation of case studies findings research has know the better way and system in the restaurant appliances from space to other spaces. Concepts and style in design have suitable for family restaurant and can reflect the comfortable feels for the customers and workers. Furthermore, concepts and images can bring positive value and experience for customers and workers. Intimate bonding and simple modern style is concept for project to bond of relationship of family or any relation between human. Existing restaurant of project have problem in the concept not related in the design, from the furniture selected and design of interior. Space of existing restaurant also limited for designing the special restaurant. Design solutions proposed for the restaurant is find the larger building and make the different design for Ayam Penyet Restaurant based on the originated of the recipes of Ayam Penyet from Indonesia and add the simple craft of carving to applied in interior.